Pengaruh Desain Manajemen Kerja Tim Agensi Olround Studio Terhadap Efisiensi Dan Efektivitas Kinerja - Hanna Agustin; Tamariska Felicia Levina Adino; Samantha Handriyni Teguh Wijaya; Jade Victoria Fortuna (Universitas Ciputra Surabaya, 2022)
A design or branding agency such as Olround Studio does not escape what is called teamwork management. Especially in the creative industry world that is familiar with brainstorming, revising, and client approval of the final result, the process of working on a project must be more dynamic and must be able to adapt to the needs and desires of the client. In this journal, we discuss aspects that need to be considered in design managing the Olround Studio’s teamwork, how to outline the workflow when handling a branding project, how to determine individual deadlines in a team, and some tips to get optimal results that are efficient to minimize revisions from clients. All discussions are reviewed from the results of reliable literature studies and case studies of well-known agencies that have experience in large-scale branding projects and also the study case of Olround Studio. As a result, it was found that the Olround Studio team was able to complete branding projects efficiently and effectively if they were committed to the timeline of each individual's work that did not exceed the agreed personal deadline. Then, the team could contribute to each other's work. The most important thing is optimal communication between team members to produce an output that was planned in the first place. All of these aspects turned out to be very influential for the whole project because one member's untimely timing could damage the time frames of other members that lead to an unsatisfied client. So that trust and loyalty of clients cannot be achieved. Keywords: Design Management, Job Description, Effectiveness, Efficiency.